2023
DOI: 10.1186/s12933-023-01818-3
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of WWP2 aggravates Type 2 diabetes mellitus-induced vascular endothelial injury through modulating ubiquitination and degradation of DDX3X

Abstract: Background Endothelial injury caused by Type 2 diabetes mellitus (T2DM) is considered as a mainstay in the pathophysiology of diabetic vascular complications (DVCs). However, the molecular mechanism of T2DM-induced endothelial injury remains largely unknown. Here, we found that endothelial WW domain-containing E3 ubiquitin protein ligase 2 (WWP2) act as a novel regulator for T2DM-induced vascular endothelial injury through modulating ubiquitination and degradation of DEAD-box helicase 3 X-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Research has shown that LMNA (lamin A/C) [314], VCAM1 [281], MAPK6 [403], DDX3X [366], SHMT2 [459], PHGDH (phosphoglycerate dehydrogenase) [560], S100A9 [433], SNCA (synuclein alpha) [335], TP63 [313], FOSL2 [1449], FHL2 [321], ATF3 [55], FOSL1 [379], DYSF (dysferlin) [475], CA4 [547], S100A8 [58] and MPO (myeloperoxidase) [521] plays an important role in the pathogenesis of lung cancer. LMNA (lamin A/C) [676], VCAM1 [657], DDX3X [708], S100A9 [745], FKBP5 [747], SNCA (synuclein alpha) [690], FOSL2 [1450], FHL2 [680], ATF3 [63], FOSL1 [718], S100A8 [67] and MPO (myeloperoxidase) [787] altered expression is associated with poor prognosis of diabetes mellitus. LMNA (lamin A/C) [676], VCAM1 [986], PHGDH (phosphoglycerate dehydrogenase) [1100], S100A9 [1045], FKBP5 [1046], FHL2 [1003], ATF3 [85] and MPO (myeloperoxidase) [1084] plays an important role in the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that LMNA (lamin A/C) [314], VCAM1 [281], MAPK6 [403], DDX3X [366], SHMT2 [459], PHGDH (phosphoglycerate dehydrogenase) [560], S100A9 [433], SNCA (synuclein alpha) [335], TP63 [313], FOSL2 [1449], FHL2 [321], ATF3 [55], FOSL1 [379], DYSF (dysferlin) [475], CA4 [547], S100A8 [58] and MPO (myeloperoxidase) [521] plays an important role in the pathogenesis of lung cancer. LMNA (lamin A/C) [676], VCAM1 [657], DDX3X [708], S100A9 [745], FKBP5 [747], SNCA (synuclein alpha) [690], FOSL2 [1450], FHL2 [680], ATF3 [63], FOSL1 [718], S100A8 [67] and MPO (myeloperoxidase) [787] altered expression is associated with poor prognosis of diabetes mellitus. LMNA (lamin A/C) [676], VCAM1 [986], PHGDH (phosphoglycerate dehydrogenase) [1100], S100A9 [1045], FKBP5 [1046], FHL2 [1003], ATF3 [85] and MPO (myeloperoxidase) [1084] plays an important role in the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…DDX3X [366], MAPK6 [403], ZFP36 [273], BHLHE40 [1451], TP63 [313], KRT17 [1452], CDC25B [556], SHMT2 [459], TRIB3 [444], PHGDH (phosphoglycerate dehydrogenase) [560], S100A8 [58], hsa-mir-410-3p [1453], hsa-mir-186-5p [1454], hsa-mir-432-5p [1455], BRCA1 [1456], FOXA1 [1457], CREB1 [1458], MAX (MYC associated factor X) [1459], ESR1 [1460], NFIC (nuclear factor I C) [1461] and STAT3 [1462] expression might be regarded as an indicator of susceptibility to lung cancer. DDX3X [708], BHLHE40 [1463], FKBP5 [747], TRIB3 [753], S100A8 [67], FOXA1 [1464], CREB1 [1465], SREBF2 [1466], ESR1 [1467] and STAT3 [1468] are a potential markers for the detection and prognosis of diabetes mellitus. A previous study reported that DDX3X [923], ZFP36 [882], FKBP5 [944], CDC25B [976], TRIB3 [948], hsa-mir-1277-5p [1469], MAX (MYC associated factor X) [1470] and STAT3 [1471] are altered expressed in respiratory viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…These mice also showed more widespread necrotic cores in plaques and enhanced macrophage infiltration and apoptosis in islets (56). Endothelial WW domain-containing E3 ubiquitin protein ligase 2 (WWP2) can preserve cell survival and prevent apoptosis by targeting DEAD-box helicase 3 X-linked (DDX3X) for K63-linked polyubiquitination and proteasomal degradation, thus preventing endothelial injury (57). In addition, knocking down nuclear factor erythroid 2-related factor 2 (Nrf2) increases apoptosis and hinders tube formation in endothelial progenitor cells (EPCs) sourced from healthy donors and wild-type mice.…”
Section: Cell Deathmentioning
confidence: 99%
“…DDX3X has been shown to play a proapoptotic role during DNA damage conditions. Thus WWP2 could be a possible target for diabetes induced vascular endothelial injury(You et al, 2023). Collectively, the UPS and its components such as E3 ligases or deubiquitinases has emerged as a promising therapeutic target for the treatment of diabetes and associated diseases.7 | CONCLUSIONSThe virtue of maintaining the balance between synthesis and degradation of key proteins involved in tissue development indicates the efficiency of embryogenesis.…”
mentioning
confidence: 99%